Influence of Aqueous Solubility-Enhancing Excipients on the Microstructural Characteristics of Furosemide-Loaded Electrospun Nanofibers - Andrea Kovács; Adrienn Kazsoki; Balázs Démuth; Bernadett Szirányi; János Madarász; Károly Süvegh; Romána Zelkó (MDPI AG, 2020)
Electrospun nanofibers were prepared from furosemide-containing hydroxypropyl cellulose and poly(vinylpyrrolidone) aqueous solutions using different solubility enhancers. In one case, a solubilizer, triethanolamine, was applied, while in the other case a pH-modifier, sodium hydroxide, was applied. Scanning electron microscopy (SEM) was carried out for morphological characterization of the fibers. The SEM images indicated similar mean diameter size of the two fibrous formulations. However, in contrast to the NaOH-containing fibers of normal diameter distribution, the triethanolamine-containing fibers showed approximately normal diameter distribution, possibly due to their plasticizing effect and the consequent slightly ribbon-like morphology. Attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), powder X-ray diffraction (XRD) and positron annihilation lifetime spectroscopy (PALS) were applied for microstructural characterization. The FTIR measurements confirmed that furosemide salt was formed in both cases. There was no sign of any crystallinity based on the XRD measurements. However, the PALS highlighted the differences in the average o-Ps lifetime values and distributions of the furosemide-loaded fibrous formulations. The two types of electrospun nanofibrous formulations containing amorphous furosemide salt showed similar macrostructures but different microstructural characteristics depending on the type of solubility enhancers, which lead to altered storage stability.